2017
DOI: 10.1103/physrevb.95.224402
|View full text |Cite
|
Sign up to set email alerts
|

Perpendicular magnetic anisotropy in amorphous NdxCo1x thin films studied by x-ray magnetic circular dichroism

Abstract: The origin of perpendicular magnetic anisotropy (PMA) in amorphous Nd x Co 1−x thin films is investigated using x-ray magnetic circular dichroism (XMCD) spectroscopy at the Co L 2,3 and Nd M 4,5 edges. The magnetic orbital and spin moments of the 3d cobalt and 4f neodymium electrons were measured as a function of the magnetic field orientation, neodymium concentration, and temperature. In all the studied samples, the magnetic anisotropy of the neodymium subnetwork is always oriented perpendicular to the plane,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 76 publications
5
13
0
Order By: Relevance
“…The general features are in agreement with former results on GdCo films [22] showing Gd surfactant and oxidation effects. This also supports a thickness dependence of the magnetic properties of the samples, as demonstrated in the following but in old and recent papers as well [23][24][25][26][27][28]. We next discuss how this bias in the effective composition impacts on magnetic properties.…”
Section: Scanning Transmission Electron Microscopy: Depth Resolvedsupporting
confidence: 84%
“…The general features are in agreement with former results on GdCo films [22] showing Gd surfactant and oxidation effects. This also supports a thickness dependence of the magnetic properties of the samples, as demonstrated in the following but in old and recent papers as well [23][24][25][26][27][28]. We next discuss how this bias in the effective composition impacts on magnetic properties.…”
Section: Scanning Transmission Electron Microscopy: Depth Resolvedsupporting
confidence: 84%
“…A similar effect, although much more pronounced than in the present case, has been observed in NdCo films [21]. The effect was demonstrated to be caused by a portion of paramagnetic Nd.…”
Section: A Magnetometrysupporting
confidence: 89%
“…Such effects should be stronger at the surface whose assumed larger RE concentration is driven by RE-RE bonding preference. Previous XMCD studies in NdCo alloys conducted by us using TEY detection [21] reported a substantial proportion of RE atoms that behaved as a paramagnetic, indicating that not all the RE atoms probed might have the same exchange interaction strength with the TM and, therefore, the same magnetic orientation distribution. Although those experiments were sensitive to the surface, their exact distribution was not demonstrated.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…On the one hand, varying the Co concentration (x = 5, 7.5, and 9) in the NdCo x film allows the modification of the strength of its PMA. A maximum has been found for x = 5, whereas higher or lower Co concentrations lead to a gradually weaker PMA, respectively [29,30]. On the other hand, by adjusting the Al spacer thickness (t = 0 nm, 2.5 nm, 5 nm, and 10 nm), the type of coupling between the two magnetic layers can be set to either direct exchange coupling (t ≤ 1.5 nm) or stray field coupling (t ≥ 2.5 nm).…”
Section: Ndco/al/py Layered Structuresmentioning
confidence: 99%